Pengaruh Bimbingan Klasikal Terhadap Pemahaman Studi Lanjut Peserta Didik - Prihatini, Anggi (IJoCE: Indonesian Journal of Counseling and Education, 2023)
An understanding of advanced studies is important for students to have as a provision in determining the choice of further studies after graduating from a level of education. In this case, the school or counseling teacher provides classical guidance regarding advanced studies to provide understanding to students as a provision in determining the choice of secondary school. This study aims to examine the effect of classical guidance on the understanding of advanced studies of class IX students at SMP Negeri 5 Muntok. The research method used is a quantitative pre-experiment with a pretest-posttest design. The results showed that classical guidance had an influence on students’ understanding of advanced studies. This can be seen in the students’ pretest scores which show an average gain of 12.93 and a posttest of 20.85. The results of hypothesis testing using the Wilcoxon signed ranks test show that the value is 0.00 which means Asymp. Sig. (2-tailed) < 0.05. So, the research hypothesis is that H0 is rejected and Ha is accepted, which means that there is an influence of classical guidance on the level of understanding of students’ advanced studies.